Graduación. (UNED, 2023)
Aparece Carlos Luis Fallas Monge - Vicerrector Ejecutivo, Jorge Enrique Guier Esquivel - Vicerrector Académico, Chester Zelaya Goodman - Rector, Marco Vinicio Álvarez Amador - Vicerrector de Planificación